2018
DOI: 10.1177/0272431618791280
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction and Depressive Symptoms on the Threshold to Adolescence: Examining Gender Differences in Depressive Symptoms and the Impact of Social Support

Abstract: The current study focused on the relationship between body dissatisfaction and depressive symptoms on the threshold of adolescence. We aimed to investigate the role of body dissatisfaction in gender differences in depressive symptoms, as well as the impact of social support from peers and parents. Mediation and moderation analyses were based on self-reports from a Norwegian population-based sample (the Tracking Opportunities and Problems Study) of 12- to 13-year-olds ( N = 547). Body dissatisfaction explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 77 publications
2
13
0
2
Order By: Relevance
“…The present findings go along with previous studies suggesting that body dissatisfaction is a predictor of depressive symptoms [ 25 , 26 , 27 , 28 ]. This relationship can be explained by the self-discrepancy theory [ 41 ], as body dissatisfaction was measured as the discrepancy between the actual and the ideal body perceived by the adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings go along with previous studies suggesting that body dissatisfaction is a predictor of depressive symptoms [ 25 , 26 , 27 , 28 ]. This relationship can be explained by the self-discrepancy theory [ 41 ], as body dissatisfaction was measured as the discrepancy between the actual and the ideal body perceived by the adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…This specific dimension of body image has been pointed as a risk factor for several health-related problems, such as quality of life [ 22 ], risky health behaviors (smoking, drug use, self-harm, etc.) [ 23 ], eating disorders [ 24 ], and depression [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sex was a moderator in the direction predicted on the indirect effect through dysphoria. In agreement with this results, Morken, Røysamb, Nilsen, and Karevold () found that girls in the general population aged 12 and 13 showed more dissatisfaction with their physical appearance and showed more depressive symptoms than boys. However, no moderation by sex was found on ideas of reference.…”
Section: Discussionsupporting
confidence: 66%
“…Body dissatisfaction, the negative subjective evaluation of one's body, is a predominant risk factor for depression, emotional distress, and low self-esteem (Duchesne et al, 2017;Morken, 2019;Van Den Berg et al, 2010). Body dissatisfaction has been reported by around 19% (Rashmi et al, 2016) to 33.3% (Priya, 2010) of female Indian college students.…”
Section: Introductionmentioning
confidence: 99%